2006
DOI: 10.1017/s0022215106002428
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interleukin 10, 12 and 18 levels in patients with head and neck cancer

Abstract: Head and neck squamous cell carcinoma (HNSCC) is an aggressive epithelial malignancy. It is the most common neoplasm arising in the upper aerodigestive tract. Interleukin (IL) 12 and IL-18 are cytokines which have a major anti-tumour activity via stimulation of a T-helper type 1 (Th1) immune response. Interleukin 10, a potent antagonist of IL-12, is a cytokine which possesses immunosuppressive activity mainly produced via T-helper type 2 (Th2) cells. Studies of other types of cancer have shown that the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
3
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 19 publications
(25 reference statements)
2
44
3
4
Order By: Relevance
“…Many studies had demonstrated that the Th1/Th2 balance was closely correlated with the outcome of many diseases [4], Many studies had demonstrated that the Th1/Th2 balance was closely correlated with the outcome of many diseases [4]. Such as, Leishmania major [5], Schistosoma japonicum [6], tuberculosis [7], head and neck cancer [8] and multiple myeloma [9]. In addition, the direction of T cells polarization determined the prognosis of many infectious diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had demonstrated that the Th1/Th2 balance was closely correlated with the outcome of many diseases [4], Many studies had demonstrated that the Th1/Th2 balance was closely correlated with the outcome of many diseases [4]. Such as, Leishmania major [5], Schistosoma japonicum [6], tuberculosis [7], head and neck cancer [8] and multiple myeloma [9]. In addition, the direction of T cells polarization determined the prognosis of many infectious diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%
“…IL10 has both tumor-promoting and tumorinhibiting properties. Higher serum and peri-tumoral IL10 levels had been reported in many malignancies (Jebreel et al, 2007). To date, lines of research have investigated the contributions of IL10 gene polymor¬phisms to the predisposition to different cancer types, such as oral, stomach, liver, breast, ovarian, cervical, prostate, and so on (Howell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Prace naukowe dotyczące niejednorodnych grup raków regionu głowy i szyi, w których analizowano związki między zjawiskami immunologicznymi i cechami kliniczno-morfologicznymi guza nowotworowego, dotyczyły wyłącznie typowych wykładników histopatologicznych, tzn. kryteriów klasyfikacji TNM i stopnia klinicznego zaawansowania choroby (S), które nie pozwalają na jednoznaczną ocenę stopnia agresywności i inwazyjności nacieku, a tym bardziej nie stanowią wystarczającego i samodzielnego wskaźnika zaawansowania procesu nowotworowego [16,33,36,[40][41][42][43][44][45] dyskusji wybrano te publikacje, w których autorzy analizowali wybrane wykładniki odpowiedzi immunologicznej typu komórkowego w odniesieniu do cech morfologicznych guzów nowotworowych u pacjentów z HNSCC, ze zbliżonym do analizowanej grupy profilem klinicznym.…”
Section: Dyskusjaunclassified
“…Uzyskane w pracy wyniki oraz dane innych autorów przedstawione w dostępnym piśmien-nictwie, dotyczące wzajemnych związków między stężeniem generowanych cytokin a wykładnikami klasyfikacji TNM, nie zawsze są zbieżne. Obserwacje badaczy dowodzą istnienia wielorakich zależności między analizowanymi wskaźnika-mi immunologiczno-klinicznymi, niedającymi się jednak zdefiniować jednoznacznie, zwłaszcza w niejednorodnej grupie HNSCC, oraz wskazują na konieczność ujednolicenia kryteriów doboru grup badawczych i wyboru materiału biologicznego, jak również indywidualnego podejścia w interpretacji wyników dotyczących danego typu guza nowotworowego do wyciągnięcia wiążących wniosków [36,[43][44][45][49][50][51].…”
Section: Dyskusjaunclassified
See 1 more Smart Citation